Conjugation of Porphyrin to Nanohybrid Cerasomes for Photodynamic Diagnosis and Therapy of Cancer - Liang, Xiaolong; Li, Xiaoda; Yue, Xiuli; Dai, Zhifei (Angewandte Chemie International Edition, 2011)
Shining light on cancer cells: A cerasomal photosensitizer of high stability and loading efficiency was developed by conjugation of a porphyrin molecule to an organoalkoxysilylated lipid followed by sol–gel and self‐assembly processes (see picture). This nanoformulation showed intrinsic fluorescence and significant damage to tumor cells under photoirradiation.